Specific antibodies and sensitive immunoassays for the human epidermal growth factor receptors (HER2, HER3, and HER4) - Marianne Nordlund Broughton; Arne Westgaard; Elisabeth Paus; Miriam Øijordsbakken; Karoline J Henanger; Bjørn Naume; Trine Bjøro (Tumor Biology, 2017)
The use of trastuzumab in patients with breast cancer that overexpresses human epidermal growth factor receptor 2 has significantly improved treatment outcomes. However, a substantial proportion of this patient group still experiences progression of the disease after receiving the drug. Evaluation of the changes in expression of the human epidermal growth factor receptors could be of interest. Monoclonal antibodies against the extracellular domain of the human growth factor receptors, 2, 3, and 4, have been raised, and specific and sensitive immunoassays have been established. Sera from healthy individuals (Nordic Reference Interval Project and Database) were analyzed in the human epidermal growth factor receptor 2 assay (N = 805) and the human epidermal growth factor receptor 3 and 4 assays (N = 114), and reference limits were calculated. In addition, sera from 208 individual patients with breast cancer were tested in all three assays. Finally, the human epidermal growth factor receptor 2 assay was compared with a chemiluminescent immunoassay for serum human epidermal growth factor receptor 2/neu. Reference values were as follows: human epidermal growth factor receptor 2, <2.5 µg/L; human epidermal growth factor receptor 3, <2.8 µg/L; and human epidermal growth factor receptor 4, <1.8 µg/L. There were significant differences in human epidermal growth factor receptor 2 and human epidermal growth factor receptor 3 serum levels between the patients with tissue human epidermal growth factor receptor 2–positive and tissue human epidermal growth factor receptor 2–negative ( p  = 0.0026, p  = 0.000011) tumors, but not in the serum levels of human epidermal growth factor receptor 4 ( p  = 0.054). There was good agreement between the in-house human epidermal growth factor receptor 2 assay and the chemiluminescent immunoassay. Our new specific antibodies for all the three human epidermal growth factor receptors may prove valuable in the development of novel anti-human epidermal growth factor receptor targeted therapies with sensitive immunoassays for measuring serum levels of the respective targets and in monitoring established treatment.